DNA Immunization against Herpes Simplex Virus: Enhanced Efficacy Using a Sindbis Virus-Based Vector - Hariharan, Mangala J. (American Society for Microbiology, 1998)
Previously we reported the development of a plasmid DNA expression vector system derived from Sindbis virus (T. W. Dubensky, Jr., et al., J. Virol. 70:508–519, 1996). In vitro, such vectors exhibit high-level heterologous gene expression via self-amplifying cytoplasmic RNA replication. In the present study, we demonstrated the in vivo efficacy of the Sindbis virus-based pSIN vectors as DNA vaccines. A single intramuscular immunization of BALB/c mice with pSIN vectors expressing the glycoprotein B of herpes simplex virus type 1 induced a broad spectrum of immune responses, including virus-specific antibodies, cytotoxic T cells, and protection from lethal virus challenge in two different murine models. In addition, dosing studies demonstrated that the pSIN vectors were superior to a conventional plasmid DNA vector in the induction of all immune parameters tested. In general, 100- to 1,000-fold-lower doses of pSIN were needed to induce the same level of responsiveness as that achieved with the conventional plasmid DNA vector. In some instances, significant immune responses were induced with a single dose of pSIN as low as 10 ng/mouse. These results indicate the potential usefulness of alphavirus-based vectors for DNA immunization in general and more specifically as a herpes simplex virus vaccine.